RESEARCH ON THE PRODUCTION OF MEDICAL SUITS BASED ON FLAX FIBER FABRICS (Journal of Science-Innovative Research in Uzbekistan, 2025)
This article examines the possibilities of using linen gauze in the production of medical gowns. The naturalness, ecological purity and hygienic properties of flax fiber have been evaluated as a suitable material for use in the field of medicine. In the study, aspects such as air permeability, natural protective properties against bacteria and the ability to protect the skin of the linen fabric are analyzed.